TES KEBAHASAN - Rina Suci Andriani (Universitas Pesantren Tinggi Darul Ulum Jombang, 2014)
Rina Suci Andriani Mahasiswa Program Pascasarjana Unesa – Surabaya rinaunipdu@gmail.com Abstract The language test intended to measure the students' communicative abilities in this case is the student communicative test in the target language and not merely in the form of the final or summative test. In the process, the good one is the test in the process, during the ongoing process of learning. The purpose of this test is to show and fix the mistakes or errors made by the students. The language test to measure the student learning outcomes should be appropriate to the nature of language teaching conducted. The forms and nature of the test is so bound to the nature of language teaching applied. The Javanese language teaching for children whose mother‟s mother tongue is Javanese will certainly be different from the teaching of Bahasa Indonesia as a second language. It is because the children have mastered the language for communication purposes both representatively and productively. The Differences of the nature and status of the teaching of the languages require different language tests for language learners, especially concerning the scope of material and level of difficulty of the test items. Keywords: language test, students, teaching and learning process Abstrak Tes kebahasaan yang dimaksudkan untuk mengukur kemampuan komunikatif siswa Dalam hal ini yaitu tes komunikatif siswa dalam bahasa target dan tidak semata-mata hanya berupa tes akhir atau sumatif saja. Dalam proses tersebut yang baik adalah tes dalam proses, selama masih berlangsung proses pembelajaran. Tujuan dari tes ini yaitu menunjukkan dan memperbaiki kesalahan-kesalahan yang dilakukan siswa. Tes kebahasaan yang dimaksudkan mengukur hasil belajar siswa hendaknya sesuai dengan sifat pengajaran bahasa yang dilakukan. Wujud dan sifat tes sangat terikat sifat pengajaran bahasa yang dikenakan kepada siswa di sekolah yang bersangkutan. Pengajaran bahasa Jawa bagi anak-anak yang berbahasa ibu bahasa jawa tentunya akan berbeda dengan pengajaran bahasa Indonesia yang merupakan bahasa kedua. Hal itu disebabkan anak-anak telah menguasai bahasa untuk keperluan komunikasinya baik bersifat representative maupun produktif. Perbedaan sifat dan kedudukan pengajaran bahasa tersebut menuntut perbedaan tes kebahasaan bagi siswa pembelajar bahasa khususnya yang menyangkut cakupan bahan dan tingkat kesulitan butir- butir tes. Kata Kunci: Tes Kebahasaan, siswa, proses belajar mengajar